2016
DOI: 10.1021/acs.biochem.6b00711
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the C-Terminal Helical Repeat Domain of Eukaryotic Elongation Factor 2 Kinase

Abstract: Eukaryotic elongation factor 2 kinase (eEF-2K) phosphorylates its only known physiological substrate, elongation factor 2 (eEF-2), which reduces the affinity of eEF-2 for the ribosome and results in an overall reduction in protein translation rates. The C-terminal region of eEF-2K, that is predicted to contain several SEL-1 like helical repeats (SLRs), is required for the phosphorylation of eEF-2. Using solution NMR methodology, we have determined the structure of a 99-residue fragment from the extreme C-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…The C-terminal part of eEF2K contains four predicted SEL1-like α-helical motifs; such motifs are often involved in protein–protein interactions [ 14 ] ( Figure 1 ). Although this C-terminal region and the extreme C-terminal end of eEF2K are required for it to phosphorylate eEF2, structural studies suggest that at least the last 99 amino acids do not provide a primary binding site for eEF2 [ 15 ]. At the extreme C-terminus is a short, highly conserved sequence that is critical for the ability of eEF2k to phosphorylate eEF2 [ 16 ].…”
Section: The Eef2k Proteinmentioning
confidence: 99%
“…The C-terminal part of eEF2K contains four predicted SEL1-like α-helical motifs; such motifs are often involved in protein–protein interactions [ 14 ] ( Figure 1 ). Although this C-terminal region and the extreme C-terminal end of eEF2K are required for it to phosphorylate eEF2, structural studies suggest that at least the last 99 amino acids do not provide a primary binding site for eEF2 [ 15 ]. At the extreme C-terminus is a short, highly conserved sequence that is critical for the ability of eEF2k to phosphorylate eEF2 [ 16 ].…”
Section: The Eef2k Proteinmentioning
confidence: 99%
“…The C-terminal region of eEF-2K has been predicted to contain the binding site for the substrate eEF-2 27 . In our earlier studies we had found that eEF-2K 627-725 was unable to inhibit the phosphorylation of eEF-2 by eEF-2K under our experimental conditions, leading us to conclude that the binding site of eEF-2 was not wholly contained within this region of eEF-2K 34 . We tested if the longer eEF-2K 562-725 construct was able to bind eEF-2 using a combination of NMR methods.…”
Section: Nmr Analyses Of the Interaction Between Eef-2k 562-725 And Ementioning
confidence: 49%
“…While S689 also deviates from Ala expected at this position, these two residue types share comparable steric profiles and helical propensities. The divergence of position 671 from the consensus (charged vs hydrophobic), was also noted in the structure of eEF-2K 627-725 , and it was found to not adversely impact the packing of helix B −1 with the A −1 and Cp helices 34 . However, due to the disorder in the nascent B −2 helix in the structure of eEF-2K 627-725 , this residue was found to be mostly solvent exposed.…”
Section: Similarities Between Eef-2k 562-725 and Other Helical Repeatmentioning
confidence: 86%
See 2 more Smart Citations